Palliative care needs evaluation in untreated patients with hepatocellular carcinoma in Ibadan, Nigeria (2010)
AIM This study aimed to evaluate the physical, psychosocial and spiritual needs of untreated patients with hepatocellular carcinoma, in order to determine effective palliative care approach and therefore improve their quality of life when curative therapy is elusive. METHODS The modified Needs Evaluation Questionnaire (NEQ) on pain and psychological assessments, thoughts and feelings and spiritual concerns was administered to 205 consecutive patients with recently diagnosed hepatocellular carcinoma after informed consent. The questionnaire included questions on pain, psychological state of mind, interference of disease with life, family functioning, knowledge of the disease, sexual functions and spirituality, among others. Responses were collated and analysed using simple statistics. RESULTS Abdominal pain, abdominal swelling, and weight loss were the leading clinical features, occurring in 157 (77%), 143 (70%) and 91 (44%) patients respectively. Pain characteristics varied, with 179 (87%) having it at presentation. Most of the patients (116, 57%) used NSAIDs for pain relief. Less than half (98, 48%) wanted to know the cause of the cancer, while 157 (77%) wanted to know treatment options. The majority (189, 92%) were ignorant about anyone with a similar ailment. Sexual function was not perceived as a problem but some expressed fears about sex, feeling that their partners would not find them attractive. Self-esteem was high in almost all respondents. Most (177, 86%) felt God is a “doer” while 28 (14%) felt God is a “supporter” and 162 (79%) would like a therapist or religious leader to talk to them. CONCLUSION Pain was a major concern and spiritual support by religious leaders was desired. Self-esteem of patients should be preserved and reinforced. We recommend that palliative care and end-of-life issues should be made part of multidisciplinary care of cancer patients in our setting